Glucose Availability and AMP-Activated Protein Kinase Link Energy Metabolism and Innate Immunity in the Bovine Endometrium. - Matthew L Turner; James G Cronin; Pablo G Noleto; I Martin Sheldon (PLoS ONE)
Defences against the bacteria that usually infect the endometrium of postpartum cattle are impaired when there is metabolic energy stress, leading to endometritis and infertility. The endometrial response to bacteria depends on innate immunity, with recognition of pathogen-associated molecular patterns stimulating inflammation, characterised by secretion of interleukin (IL)-1β, IL-6 and IL-8. How metabolic stress impacts tissue responses to pathogens is unclear, but integration of energy metabolism and innate immunity means that stressing one system might affect the other. Here we tested the hypothesis that homeostatic pathways integrate energy metabolism and innate immunity in bovine endometrial tissue. Glucose deprivation reduced the secretion of IL-1β, IL-6 and IL-8 from ex vivo organ cultures of bovine endometrium challenged with the pathogen-associated molecular patterns lipopolysaccharide and bacterial lipopeptide. Endometrial inflammatory responses to lipopolysaccharide were also reduced by small molecules that activate or inhibit the intracellular sensor of energy, AMP-activated protein kinase (AMPK). However, inhibition of mammalian target of rapamycin, which is a more global metabolic sensor than AMPK, had little effect on inflammation. Similarly, endometrial inflammatory responses to lipopolysaccharide were not affected by insulin-like growth factor-1, which is an endocrine regulator of metabolism. Interestingly, the inflammatory responses to lipopolysaccharide increased endometrial glucose consumption and induced the Warburg effect, which could exacerbate deficits in glucose availability in the tissue. In conclusion, metabolic energy stress perturbed inflammatory responses to pathogen-associated molecular patterns in bovine endometrial tissue, and the most fundamental regulators of cellular energy, glucose availability and AMPK, had the greatest impact on innate immunity.